Malaysia : From Crisis to Recovery - Khatri, Yougesh (Occasional Papers; Occasional Paper ;, 2001)
This paper discusses how Malaysia can better protect itself from future shocks and avoid another crisis while it seeks to regain its position as one of the fastest growing economies in the world. To these ends, its strategy should include continued structural reforms to achieve healthy balance sheets of the banking and corporate sectors; further deregulation to promote competition and efficiency; and consistent macroeconomic policies to maintain financial stability and sustainable fiscal and external positions. Malaysia's economic structure and performance were relatively strong prior to the crisis. Malaysia's initial low level of short-term external debt enabled it to maintain foreign reserves at a reasonably high level, and this contributed to relatively robust external and domestic confidence early on in the crisis. As a consequence of financial vigilance exercised through prudential regulation of capital movements, the exposure of the financial and corporate systems was contained. Stock market capitalization in Malaysia grew to an extremely high level prior to the crisis, reflecting both the fast expansion of the capital market and liberal capital account regime.